Low-temperature plasmas induced in nitrogen by extreme ultraviolet (EUV) pulses. (25th January 2018) - Bartnik, A.; Skrzeczanowski, W.; Fiedorowicz, H.; Wachulak, P.; Fok, T.
Abstract: In this work, a comparative study of low-temperature plasmas, induced in a gaseous nitrogen by photoionization of the gas using two different irradiation systems, was performed. Both systems were based on laser-produced Xe plasmas, emitting intense extreme ultraviolet (EUV) radiation pulses in a wide wavelength range. The essential difference between the systems concerned formation of the EUV beam. The first one utilized a dedicated ellipsoidal mirror for collecting and focusing of the EUV radiation. This way a high radiation fluence could be obtained for ionization of the N2 gas injected into the vacuum chamber. The second system did not contain any EUV collector. In this case, the nitrogen to be ionized was injected into the vicinity of the Xe plasma. In both cases, energies of emitted photons were sufficient for dissociative ionization, ionization of atoms or even ions. The resulting photoelectrons had also sufficiently high energy for further ionizations or excitations. Low-temperature plasmas, created this way, were investigated by spectral measurements in the EUV, ultraviolet (UV) and visible (VIS) spectral ranges. Time-resolved UV/VIS spectra, corresponding to single-charged ions, molecules, and molecular ions, were recorded. Numerical simulations of the molecular spectra were performed allowing one to estimate vibrational and rotational temperatures of plasmas created using both irradiation systems.